Assessment of condyle, masseter and temporal muscles volumes in patients with juvenile systemic lupus erythematosus: A cross-sectional study - Sandra Lucia Golin; Nailu Angélica Sinicato; Karyna Valle-Corotti; Acácio Fuziy; Ana Carla Nahas-Scocate; Simone Appenzeller; Andre Luiz Ferreira Costa (Elsevier, 2017)
Aims: The purpose of this study was to evaluate the effect of the corticosteroid therapy for both treatment of juvenile systemic lupus erythematosus and disease activity on two masticatory muscles and condyle of the temporomandibular joint. Methods: A total of 21 controls and 48 juvenile systemic lupus erythematosus patients were investigated. Volumes of the temporal and masseter muscles and condyle of the subjects were assessed by using a 3D reconstruction in magnetic resonance imaging. The ITK-SNAP, a medical imaging software, was used for 3D reconstruction. A dental examination with registration of occlusion was performed in subjects. Data were statistically analyzed by means of the Dahlberg's test associated with paired t-test, Fisher's exact test and Chi-square. Results: There was a positive correlation between temporalis muscle and age (p = 0.032), masseter volume (p = 0.029) and condyle volume (p = 0.013). The mean volume measurements of temporal and masseter muscles and condyle were not statistically associated with juvenile systemic lupus erythematosus regarding disease activity and corticosteroid therapy (p > 0.05). There were no significant differences between malocclusion and volume of muscles and condyle. Conclusion: This study suggested that volume of the target structures has no correlation with cumulative corticosteroid dose, disease activity, and malocclusion.